Self-Cancer Care Management in Adults During COVID-19 Pandemic: A Literature Review - Rischar Beny Riswanto; Nikma Alfi Rosida; Angga Miftakhul Nizar (Critical Medical and Surgical Nursing Journal (CMSNJ), 2022)
Introduction: The coronavirus disease of 2019 (COVID-19) is a particularly hazardous virus due to its rapid transmission. The spread of COVID-19 is so rapid that the WHO has labeled it a pandemic, and Indonesia has declared it a national catastrophe. The purpose of this essay was to summarize the management of cancer patient care during the COVID-19 epidemic. Methods: In this review, we used the PRISMA method and article sources from databases, including Scopus, Science Direct, SAGE, and CINAHL/EBSCO, from the years 2019 to 2020.. Inclusion criteria include research conducted in human, using nursing management strategies in cancer patients, and article written inEnglish and have been published in 2020. Exclusion criteria include research on non-human, articles that did not mention cancer care management during the COVID-19 epidemic, review and survey studies. Result: This review looked at 14 articles from different nations. Two studies used phone massage as an intervention, three studies used a combination of phone massage and phone call with smartphone technology, five studies used a video call to monitor cancer care management, one study used email or social media to monitor cancer care management, and three studies used web applications that are connected to the internet. Conclusion: In conclusion, our findings suggest that continuing anticancer treatment during the COVID-19 pandemic is safe and possible if appropriate and stringent infection control measures are implemented. In the future, more extensive research of COVID-19 infection in cancer patients may aid in the care of oncology patients